Routledge handbook of sport and exercise systems genetics - Lightfoot, J. Timothy; Hubal, Monica J.; Roth, Stephen M., 1973- (Routledge international handbooks., 2019)
"The Routledge Handbook of Sport and Exercise Systems Genetics constitutes the most authoritative and comprehensive reference in this critical area of study, consolidating knowledge and providing a framework for interpreting future research findings. Taking an approach which covers single gene variations, through genomics, epigenetics and proteomics, to environmental and dietary influences on genetic mechanisms, the book is divided into six sections. It examines state-of-the-art genetic methods, applies its approach to physical activity, exercise endurance, muscle strength and sports performance, and discusses the ethical considerations associated with genetic research in sport and exercise"--